2022
DOI: 10.3390/ijerph192013023
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Adverse Mental Health Issues in the Thai Population during the Coronavirus Disease 2019 Pandemic

Abstract: In light of the coronavirus disease 2019 (COVID-19) pandemic and the enormous amount of uncertainty caused by it, mental health issues have become a great concern. Evidence regarding the effects of psychological resilience on the Thai population is scarce. We evaluated psychological resilience during the first wave of the COVID-19 pandemic and its association with the risk of mental health outcomes, such as depression, anxiety, stress, and health-related well-being. This cross-sectional study was a part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…Moreover, it can be explained by the successful attempt of the hospital in developing holistic clinical practice guidelines for the care of our patients. Most of the participants in this study had a normal or high RQ level, which is inconsistent with a previous study in Thailand during 2020 that found 43.9% of the participants had a low resilience quotient level, with a mean score on the Brief Resilient Coping Score (BRCS) of 13.9 (SD 4-20) [22]. This difference could be from the timing of the collection the data that suggested the RQ was changeable and adapted along with time.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, it can be explained by the successful attempt of the hospital in developing holistic clinical practice guidelines for the care of our patients. Most of the participants in this study had a normal or high RQ level, which is inconsistent with a previous study in Thailand during 2020 that found 43.9% of the participants had a low resilience quotient level, with a mean score on the Brief Resilient Coping Score (BRCS) of 13.9 (SD 4-20) [22]. This difference could be from the timing of the collection the data that suggested the RQ was changeable and adapted along with time.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the outcomes were consistent with a global general population survey which found that over 25% of persons lacked psychological resilience, with younger people having lower psychological resilience ( 37 ). Similar findings were found in another study on the general population of Thailand, where more than 80% of participants had psychological resilience scores ranging from low to medium during the COVID-19 epidemic ( 38 ).…”
Section: Discussionsupporting
confidence: 88%
“…Previous COVID‐19 related studies highlighted the importance of developing interventions that enhance resilience to reduce negative mental effects during pandemics (Skalski et al, 2022; Verdolini et al, 2021), with the main focus on individuals' confidence in their judgements, their self‐efficacy and realistic expectations (self‐perception) (Hjemdal et al, 2011; Pereira et al, 2013). Some authors state the need to prioritize psychological resilience as a primary public health issue during stressful situations like pandemics (Ruengorn et al, 2022).…”
Section: Discussionmentioning
confidence: 99%